Weakly induced modifications of I-fuzzy topologies - Yueli Yue; Jinming Fang (International Journal of Mathematics and Mathematical Sciences)
The aim of this paper is to study weakly induced I-fuzzy topological spaces and weakly induced modifications of I-fuzzy topologies. We give two kinds of weakly induced I-fuzzy topologies for each I-fuzzy topology and prove that I-WIFTOP is a reflective and coreflective full subcategory of I-FTOP. We also discuss some relationships between several categories.